2015
DOI: 10.1016/j.celrep.2015.08.046
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Super-Enhancer Activity in Autoinflammatory Site-Derived T Cells Reduces Disease-Associated Gene Expression

Abstract: The underlying molecular mechanisms for many autoimmune diseases are poorly understood. Juvenile idiopathic arthritis (JIA) is an exceptionally well-suited model for studying autoimmune diseases due to its early onset and the possibility to analyze cells derived from the site of inflammation. Epigenetic profiling, utilizing primary JIA patient-derived cells, can contribute to the understanding of autoimmune diseases. With H3K27ac chromatin immunoprecipitation, we identified a disease-specific, inflammation-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 26 publications
5
105
0
Order By: Relevance
“…ChIP-seq also revealed the alterations of H3K27ac in autoimmune disease [46], such as Crohn's disease [47] and juvenile idiopathic arthritis [10] and in neurodegenerative disease like Parkinson's disease [48]. In these cases, disease-associated SNPs often reside in enhancers or super-enhancers.…”
Section: H3k27ac and H3k4me1/2mentioning
confidence: 96%
See 2 more Smart Citations
“…ChIP-seq also revealed the alterations of H3K27ac in autoimmune disease [46], such as Crohn's disease [47] and juvenile idiopathic arthritis [10] and in neurodegenerative disease like Parkinson's disease [48]. In these cases, disease-associated SNPs often reside in enhancers or super-enhancers.…”
Section: H3k27ac and H3k4me1/2mentioning
confidence: 96%
“…There are several hundred chromatin regulators in the human genome that encode enzymes that 'write,' 'read' or 'remove' histone modifications [28]. Chromatin regulators are emerging therapeutic targets of the epigenetic drugs in cancer [45,52] and noncancer disease therapy [10]. Histone deacetylase and Janus kinase 2 (a histone phosphorylation writer) inhibitors have been approved for cancer therapy [63], and more epigenetic drugs are currently in clinical or preclinical trials [21,45].…”
Section: Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the BET inhibitors JQ1, I-BET762 and I-BET151 were shown to reduce the production of proinflammatory cytokines in monocytes and macrophages stimulated by LPS in vitro and in mice 120. Studies on human inflamed joint synovial fluid show that treatment with JQ1 on CD4+ memory/effector T cells preferentially inhibited the expression of genes involved in proinflammatory and cytokine-related processes regulated by super-enhancers 121. Although BET inhibitors have not been studied in the context of IBD, their immune-modulating potential points to promising effects for IBD treatment.…”
Section: Dres As Therapeutic Targetsmentioning
confidence: 99%
“…In mammalian cells, thousands of enhancers are active and up to 1 million enhancers have been postulated to be active in all human cells (93). Super enhancers are clusters of typical enhancers marked by a very high density of the p300 histone acetyltransferase and H3K27Ac (9496). Transcription factor density at these regions is also particularly high and seminal work by Richard Young and colleagues has found that these regions are particularly sensitive to perturbation of Mediator and members of the bromodoman and extraterminal (BET) subfamily of bromodomain proteins (94, 96).…”
Section: Super Enhancers and Typical Enhancersmentioning
confidence: 99%